Cucurbitane Triterpenoid from Momordica charantia Induces Apoptosis and Autophagy in Breast Cancer Cells, in Part, through Peroxisome Proliferator-Activated Receptor γ Activation. (13th June 2013) - Weng, Jing-Ru; Bai, Li-Yuan; Chiu, Chang-Fang; Hu, Jing-Lan; Chiu, Shih-Jiuan; Wu, Chia-Yung
Abstract : Although the antitumor activity of the crude extract of wild bitter gourd ( Momordica charantia L.) has been reported, its bioactive constituents and the underlying mechanism remain undefined. Here, we report that 3 β, 7 β -dihydroxy-25-methoxycucurbita-5, 23-diene-19-al (DMC), a cucurbitane-type triterpene isolated from wild bitter gourd, induced apoptotic death in breast cancer cells through peroxisome proliferator-activated receptor (PPAR) γ activation. Luciferase reporter assays indicated the ability of DMC to activate PPAR γ, and pharmacological inhibition of PPAR γ protected cells from DMC's antiproliferative effect. Western blot analysis indicated that DMC suppressed the expression of many PPAR γ -targeted signaling effectors, including cyclin D1, CDK6, Bcl-2, XIAP, cyclooxygenase-2, NF- κ B, and estrogen receptor α, and induced endoplasmic reticulum stress, as manifested by the induction of GADD153 and GRP78 expression. Moreover, DMC inhibited mTOR-p70S6K signaling through Akt downregulation and AMPK activation. The ability of DMC to activate AMPK in liver kinase (LK) B1-deficient MDA-MB-231 cells suggests that this activation was independent of LKB1-regulated cellular metabolic status. However, DMC induced a cytoprotective autophagy presumably through mTOR inhibition, which could be overcome by the cotreatment with the autophagy inhibitor chloroquine. Together, the ability of DMC to modulate multiple PPAR γ -targeted signaling pathways provides a mechanistic basis to account for the antitumor activity of wild bitter gourd.